INTERVENSI PROGRESSIVE MUSCLE RELAXATION LEBIH MENURUNKAN TEKANAN DARAH DARI PADA SLOW STROKE BACK MASSAGE PADA PASIEN HIPERTENSI DERAJAT I YANG MENGONSUMSI OBAT ANTI HIPERTENSI DI BADUNG - Juni Antari, Ni Komang Ayu; Pangkahila, Alex; Ali Imron, Muh.; Griadhi, I Putu Adiartha; Sri Handari Adiputra, Luh Made Indah; Irfan, Muh. (Sport and Fitness Journal, 2019)
ABTSRACT Introduction: Physical exercise as anticipate of hypertension along with nutrition and medicines. One of physical exercise that can be applicated here is relaxation techniques which is showed positive impact in decreased blood pressure. Objective: Determine the difference between PMR intervention with SSBM intervention to reduce blood pressure for grade I hypertension patients whose consumed anti-hypertension medicine in badung regency. Methods: Experimental method Pre and post-test control group design and used 24 subjects, divided in to 2 groups, in which the experimental group I (n=12) received progressive muscle relaxation (PMR) while the treatment group 2 (n=12) received slow stroke back massage (SSBM). Intervention is given 3 times a week for 4 weeks. This study was using simple random sampling. Blood pressure was measured by sphygmomanometer and stethoscope. Result: Independent Sample T-test showed there was significant difference between Group 1 and Group 2 which (p<0.05) for systolic and diastolic blood pressure. Conclusion: Progressive muscle relaxation intervention decrease blood pressure more than slow stroke back massage intervention in patients grade I hypertension whose consumed anti-hypertension medicine in Badung Regency. Keywords: progressive muscle relaxation, slow stroke back massage, grade I hypertension, blood pressure